COP 28 and Nepal’s Climate Diplomacy - Lohani, Mohan (NCWA Annual Journal, 2024)
Climate change has become an issue of global concern in recent years. No country is immune to the impact of such change. Unrestricted emission of greenhouse gases resulting in global warming and challenging the earth’s ecosystem has threatened the very survival of mankind. Nepal, a mountainous country with rugged geographical terrain of varying altitudes, has become highly vulnerable to the impact of climate change on the living conditions of people and their livelihoods based on natural resources. Prime Minister Pushpa Kamal Dahal, addressing the 28th meeting of the Conference of Parties (COP) in Dubai last year, presented the plight of the country and forcefully pleaded for global partnership and international cooperation to cope with the climate change-induced crisis affecting the world, in particular, Least Developed Countries like Nepal with low adaptation.